Deterministic Generation of Concatenated Graph Codes from Quantum Emitters - Love A. Pettersson; Anders S. Sørensen; Stefano Paesani (PRX Quantum)
Photon loss is the dominant noise mechanism in photonic quantum technologies. Designing fault-tolerant schemes with high tolerance to loss is thus a central challenge in scaling photonic quantum information processors. Concatenation of a fault-tolerant construction with a code able to efficiently correct loss is a promising approach to achieve this but practical ways to implement code concatenation with photons have been lacking. We propose schemes for generating concatenated graph codes using multiphoton emission from two quantum emitters or a single quantum emitter coupled to a memory—capabilities available in several photonic platforms. We show that these schemes enable fault-tolerant fusion-based quantum computation in practical regimes with high photon loss and standard fusion gates without the need for auxiliary photons.